Tadeusz Buksiński, Prawo a władza polityczna, Wyd. Naukowe IF UAM, Poznań 2009, ss. 308. - CWYNAR, Katarzyna M. (Przegląd Politologiczny, 2018)
Tadeusz Buksiński, Prawo a władza polityczna, Wyd. Naukowe IF UAM, Poznań 2009, ss. 308.